Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
5x - 9 = 2x + 23
x = 10 2/3
Step-by-step explanation:
Lets convert the phrases to mathematical equations.
" five times a number" = 5 multiplied by x = 5x
"decresed by 9 " = -9
" is equal to" = "="
"twice the number" = 2 multiplied by x = 2x
"increased by 23" = +23
The final equation is 5x, -9, =, 2x, +23 or 5x - 9 = 2x + 23
We can continue to solve this problem:
5x - 9 = 2x + 23
Add 9 to both sides
5x = 2x + 32
Subtract 2x from both sides
3x = 32
Divide both sides by 3
x = 32/3 or 10 2/3
-Chetan K
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.